Pemanfaatan Ruga Palatal untuk Identifikasi Forensik - Shanty Chairani; Elza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2012)
Human identification is very important in forensic field. Analysis of teeth and other components in oral cavity can make a significant contribution in the process. Palatal rugae, which is one of the components in oral cavity, have a promising prospect in helping identification process because of its individualistic pattern. In special case whereas victim was burnt and the jaw was edentulous, which identification methods using analysis of finger print and tooth examination was not possible, analysis of palatal rugae would be very helpful in identification process. This paper will discuss application of palatal rugae analysis in forensic identification, the benefits and the limitations. Several challenges in the future so that the usage of analysis of palatal rugae becoming wider and more optimal, will also be discussed. DOI: 10.14693/jdi.v15i3.35palatal